Chick-pea yield formation under the influence of elements of cultivation technology - Каленська, С. М.; Новицька, Н. В.; Нетупська, І. Т. (Scientific Progress & Innovations, 2012)
It covers the economic and agrotechnical value of one of the most common legumes - chickpeas, and positive action for soils, on which it placed in crop rotation. Displayed beneficial influence of fertilizer and pre-seed inoculation on yield formation. The results of studies of elements of growing technology on the formation of structural elements and yield levels of Rozanna, Triumph and Pegasus varieties on typical chernozem soil. Established that the Pre-seed inoculation in combination with low doses of nitrogen fertilizers contributed to increase in yield of chick-peas varieties. The highest yield of chickpea in the experiment (4/,9 t/ha) observed in a variety Rozanna in the variant with the use of pre-inoculation of seeds on the background making N30P60K60 at 1040 sm-1 has been found.